Development of CRISPR/Cas9-based gene drive biotechnology in S. cerevisiae - Yan, Yao (Kansas State University, 2022)
The budding yeast Saccharomyces cerevisiae is a well-studied eukaryotic model organism for investigating the fundamental aspects of molecular and cellular biology. It also can be used to evaluate the technical feasibility of new technologies in eukaryotic cells. In our lab, we aimed to use Saccharomyces cerevisiae as a model to develop CRISPR/Cas9-based gene drive biotechnology. The CRISPR/Cas9 biotechnology is a powerful gene editing tool used to modify target genomic sequences in all forms of living creatures including animals, plants, fungi, and bacteria. One potential application of this molecular method is within a “gene drive” system. This unique arrangement of CRISPR within a genome may one day allow for global control of biological populations and be used to eliminate pests, parasites, and invasive species. However, there are many concerns regarding the utilization of this technology, including gene drive design, control, and development of resistance, etc. In our study, we developed an artificial gene drive system in budding yeast, which could edit multiple loci at the same time. We demonstrated that this triple gene drive system could successfully edit three DNA targets independently with only a single copy of S. pyogenes Cas9. We also found that the occurrence of NHEJ could be repressed by modifying DNA Ligase IV. However, successful gene drives still allowed for the occurrence of a small number of “resistant” clones. We investigated potential causes of this imperfect drive activity. Our work illustrated that imperfect activation of the inducible promoter driving expression of the Cas9 nuclease or issues with multiplexing to artificial sequences may have resulted in a small percentage of resistant/inactive clones. The CRISPR/Cas9 system can also be used to regulate gene transcription. This involves a mutated Cas9 variant that has lost its nuclease activity (dCas9). We developed a CRISPR/dCas9 system by tagging dCas9 with transcriptional regulators. Our experiments demonstrated that CRISPR/dCas9 could activate target gene transcription when tagged with the transcriptional activator VPR and repress gene transcription when tagged with the transcriptional repressor Mxi1.
Keywords: CRISPR; Cas9; dCas9; Gene drive